2015
DOI: 10.1124/mol.115.101618
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide Derivatives AqB007 and AqB011 Selectively Block the Aquaporin-1 Ion Channel Conductance and Slow Cancer Cell Migration

Abstract: Aquaporins (AQPs) in the major intrinsic family of proteins mediate fluxes of water and other small solutes across cell membranes. AQP1 is a water channel, and under permissive conditions, a nonselective cation channel gated by cGMP. In addition to mediating fluid transport, AQP1 expression facilitates rapid cell migration in cell types including colon cancers and glioblastoma. Work here defines new pharmacological derivatives of bumetanide that selectively inhibit the ion channel, but not the water channel, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 44 publications
7
80
0
Order By: Relevance
“…AQP1 ionic current activation is less efficient when two key residues aspartate (D237) and lysine (K243) in the carboxyl terminal domain are mutated, further indicating the C‐terminal domain influences the efficacy of cGMP‐mediated activation. Site‐directed mutagenesis of a conserved pair of arginine residues in loop D decreases the efficacy of inhibition by the AQP1 ion channel blocker AqB011 (Kourghi et al., 2017), confirming an earlier proposal that the compound interacts at the loop D gating region . AQP1‐expressing HT29 colon cancer cells treated with AqB011 show impaired cell migration at doses that match the dose‐dependent block of the ion channel conductance, recorded from cloned human AQP1 channels expressed in Xenopus oocytes .…”
Section: Functional Roles Of Mammalian Aqp1 Ion Channelssupporting
confidence: 70%
See 4 more Smart Citations
“…AQP1 ionic current activation is less efficient when two key residues aspartate (D237) and lysine (K243) in the carboxyl terminal domain are mutated, further indicating the C‐terminal domain influences the efficacy of cGMP‐mediated activation. Site‐directed mutagenesis of a conserved pair of arginine residues in loop D decreases the efficacy of inhibition by the AQP1 ion channel blocker AqB011 (Kourghi et al., 2017), confirming an earlier proposal that the compound interacts at the loop D gating region . AQP1‐expressing HT29 colon cancer cells treated with AqB011 show impaired cell migration at doses that match the dose‐dependent block of the ion channel conductance, recorded from cloned human AQP1 channels expressed in Xenopus oocytes .…”
Section: Functional Roles Of Mammalian Aqp1 Ion Channelssupporting
confidence: 70%
“…The development of selective blockers has been a long awaited milestone, and is now allowing the characterization of aquaporin functions in living cells. Block by AqB011 of the AQP1 ionic conductance demonstrated that the cation channel activity is a key component for HT29 cancer cell migration Figure . The continuing evaluation of traditional medicinal plants as sources of blockers of AQP1 has produced agents that selectively inhibit water permeability (such as bacopaside II), or that block both the water and ion channel pores (such as bacopaside I); these also are promising tools for controlling migration in the subset of cancers that rely on AQP1 expression .…”
Section: Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations